2018
DOI: 10.1159/000489390
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thromboembolic Risk Score with Left Atrial Thrombus and Spontaneous Echocardiographic Contrast in Non-Anticoagulated Nonvalvular Atrial Fibrillation Patients

Abstract: Objectives: The aim of the study was to examine the association of CHADS2/CHA2DS2-VASc scores with left atrial thrombus (LAT) and spontaneous echocardiographic contrast (SEC) in non-anticoagulated nonvalvular atrial fibrillation (NVAF) spontaneous patients, and to develop a new scoring system for LAT/SEC prediction. Methods: Consecutive non-anticoagulated NVAF patients with or without LAT/SEC by transesophageal echocardiography were identified in the Guangdong General Hospital. Results: Among 2,173 patients, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Yet, these indicators are relatively difficult to define. Consequently, recent efforts are focused on studies to refine the assessment of the risk of stroke based on cardiac structure and function [27,28]. AF has been associated with electromechanical remodeling of the LA.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these indicators are relatively difficult to define. Consequently, recent efforts are focused on studies to refine the assessment of the risk of stroke based on cardiac structure and function [27,28]. AF has been associated with electromechanical remodeling of the LA.…”
Section: Discussionmentioning
confidence: 99%
“… 5 The possible explanation is that the components of the CHADS2/CHA2DS2-VASc scores mainly contribute to the atherosclerotic process, instead of focusing on the formation of thromboembolism. 27 The current study suggested the predictive powers of CHADS2 and CHA2DS2-VASc for LAT/SEC were improved by the additions of variables including non-paroxysmal AF (2 points) and LAD >37.5 mm (1 point), especially in the population of patients at a high risk of thromboembolism. Therefore, refinement of CHADS2 and CHA2DS2-VASc scores may provide better prediction of high‑risk AF patients.…”
Section: Discussionmentioning
confidence: 68%
“…However, TEE cannot be performed in all AF patients, such as those patients who were not scheduled for AF ablation/cardioversion. While the CHA2DS2-VASc score is often used to evaluate stroke risk in patients with NVAF, the predictive value of the CHA2DS2-VASc scoring system for LASEC in NVAF is limited [ 6 ]. Therefore, establishing a risk score to noninvasively predict the presence of LASEC is necessary.…”
Section: Discussionmentioning
confidence: 99%